Understanding the Traditional Food System of First Nations in Canada in the Context of Biodiversity - Klassen, Hannah (Université d'Ottawa / University of Ottawa, 2023)
The health and well-being of Indigenous Peoples, including their nutritional status, is poor compared to the general Canadian population. There are many causes of these disparities, including racism, poor access to health resources, and the nutrition transition. Before colonization, most First Nations across Canada consumed diets purely composed of Traditional Foods (TF) that were hunted or collected from the natural environment. TF are important for their nutritional quality, food security, and culture. However, rates of TF consumption have decreased in recent years contributing to poor dietary outcomes. The diversity and quantity of TF consumed is thought to be primarily dictated by the ecological biodiversity in the surrounding environment; however, this relationship remains untested in Canada. The objective of this study was to gain a better understanding of First Nations modern food systems by evaluating the relationship between ecozone biodiversity and nutritional outcomes in the form of dietary diversity in First Nations individuals across Canada. We used dietary data and household data collected by the First Nations Food, Nutrition and Environment Study and multiple biodiversity databases for analyses. Spearman’s correlations were used to investigate the relationship between dietary diversity and nutrition. A statistical model was used to evaluate the relative predictive power of biodiversity and multiple other predictive variables in determining dietary diversity. We found that individuals who consume more TF have more nutrient rich diets, and therefore, dietary diversity is a good indicator of nutrition outcomes. We also found that in contrast to previous research and assumptions, in the context of First Nations living in Canada, biodiversity has a negative relationship to dietary species richness. It was also determined that variables related to culture, and accessibility of TF were the most important factors in predicting positive nutritional outcomes. These preliminary results provide key areas for interventions essential for increasing access to TF.
Keywords: Biodiversity; First Nations; Traditional Foods; Dietary Diversity; Canada; Ecozones